'How are you actually doing, ladies?' Indicators of gender equality through the lens of the UN Committee on the Elimination of Discrimination against Women. Issue 8 (13th September 2020) - Gilleri, Giovanna
ABSTRACT: International bodies increasingly use state-generated indicators to monitor states' compliance with international human rights law, particularly gender equality. Among these, the UN Committee on the Elimination of Discrimination against Women (Committee) encourages states to develop nationally generated gender indicators under the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW). This article examines the legal framework of gender indicators and assesses some limitations as to intersectionality, gender stereotyping and gender-based violence. Indicators constitute a central instrument to CEDAW-based reporting processes. Yet, the Committee should take seriously such challenges for the measurement not to overlook women's real-life experiences.